Hemodynamic characterization of the Realheart® total artificial heart with a hybrid cardiovascular simulator. Issue 8 (27th March 2022) - Fresiello, Libera; Najar, Azad; Brynedal Ignell, Nils; Zieliński, Krzysztof; Rocchi, Maria; Meyns, Bart; Perkins, Ina Laura
Abstract: Background: Heart failure is a growing health problem worldwide. Due to the lack of donor hearts there is a need for alternative therapies, such as total artificial hearts (TAHs). The aim of this study is to evaluate the hemodynamic performance of the Realheart® TAH, a new 4‐chamber cardiac prosthesis device. Methods: The Realheart® TAH was connected to a hybrid cardiovascular simulator with inflow connections at the left/right atrium, and outflow connections at the ascending aorta/pulmonary artery. The Realheart® TAH was tested at different pumping rates and stroke volumes. Different systemic resistances (20.0‐16.7‐13.3‐10.0 Wood units), pulmonary resistances (6.7‐3.3‐1.7 Wood units), and pulmonary/systemic arterial compliances (1.4–0.6 ml/mm Hg) were simulated. Tests were also conducted in static conditions, by imposing predefined values of preload‐afterload across the artificial ventricle. Results: The Realheart® TAH allows the operator to finely tune the delivered flow by regulating the pumping rate and stroke volume of the artificial ventricles. For a systemic resistance of 16.7 Wood units, the TAH flow ranges from 2.7 ± 0.1 to 6.9 ± 0.1 L/min. For a pulmonary resistance of 3.3 Wood units, the TAH flow ranges from 3.1 ± 0.0 to 8.2 ± 0.3 L/min. The Realheart® TAH delivered a pulse pressure ranging between ~25 mm Hg and ~50 mm Hg for the tested conditions. Conclusions: The Realheart® TAH offers great flexibility to adjust the output flow and delivers good pressure pulsatility in the vessels. Low sensitivity of device flow to the pressure drop across it was identified and a new version is under development to counteract this. Abstract : Device flow is regulated by changing the pumping rate and the stroke length (~stroke volume). Two pumping units deliver flow independently left and right: up to 6.9 L/min for a systemic circulation and 8.2 L/min for a pulmonary circulation. The device generates a pulsatile flow, with a pressure pulsatility between ~25 and ~50 mm Hg. A new device version is under development to counteract the low sensitivity of flow to the pressure drop across the device.